SISTEM INFORMASI MANAJEMEN RAPOR SISWA SMA AL-KAUTSAR BANDAR LAMPUNG - Haryono, Muhammad Harry; Yusman, Machudor; Irawati, Anie Rose (Jurnal Komputasi, 2017)
Al-Kautsar High School, under the Al-Kautsar Foundation implements a system of government-determined education by emphasize the education of Islam and Arabic. Students get a value-added report card at the end of each semester. Scoring is done by the teacher who is responsible for each subject and class being taught. The score of the student is submitted to the homeroom teacher to be arranged in such a way according to the report card format. Then the homeroom teacher handed the value to the admin to be printed into a report card. With a system like this if a mistake occurs on a file that the admin has received, he cannot immediately handle the mistake and should contact the homeroom teacher or even the responsible teacher to correct the mistake before being handed again back to homeroom teacher and admin. Based on the background and identification of the problems that have been presented, this research creates a system that can handle the problem. The system is web-based so that the score data filled by the teacher can be directly viewed, accepted, and supervised by the admin and teachers. Any score change can be done at any time before the end of the semester. The test results that email report card system to the parents of the students did not succeed but the main features of the system such as the filling of grades by teachers and homeroom teacher and printing report cards into .pdf format works well.